Seroprevalence of Canine Leishmaniasis in Sheltered Dogs in Bushehr Province, Southwest of Iran during 2022-2023 - Negar Zare; Abdollah Najm; Mehdi Mohebali; Alireza Sahebani; Mohammad Rayani; Zabihollah Zareei; Maryam Bemana; Afshin Barazesh (Iranian Journal of Parasitology)
Background: The Mediterranean form of visceral leishmaniasis (VL) is endemic in some regions of Iran and is often seen in children under 10 years old. There is a 90% mortality in patients, if diagnosis and treatment are not done on time. Canids, as reservoirs, play an important role in the spread of the disease. Methods: Bushehr Province, southern Iran is always mentioned as one of the endemic areas for VL, so for this purpose, as the first study in the region, 112 sheltered dogs in Bushehr City were evaluated for canine leishmaniasis (CanL) using serological Direct Agglutination Test (DAT) as well as detailed clinical examinations. Results: Out of 112 samples collected, 71.4% of cases had anti-L. infantum IgG antibody titers of 1:80 and higher and therefore considered as seropositive. Furthermore, from the 70 seropositive dogs with antibody titer of 1:320 and higher, 47 (42%) had at least one of the clinical symptoms associated with VL and considered as cases with CanL. Conclusion: The current seroprevalence situation of dogs in this region, is very noticeable and can be an important alarm for policymakers and health system practitioners. More comprehensive and complementary parasitological studies should be carried out on a number of reservoirs in the region for diagnosis and treatment and to accurately determine the statistics of the disease compared to the obtained seroprevalence status.